Assessing the acute effects of CDP-choline on sensory gating in schizophrenia: A pilot study. (May 2018) - Aidelbaum, Robert; Labelle, Alain; Baddeley, Ashley; Knott, Verner
Deficient sensory gating (SG) in schizophrenia is associated with functional outcome and offers a therapeutic target as it is linked to the altered function/expression of the α7 nicotinic acetylcholine receptors (nAChRs). This study analyzed the effects of citicoline (CDP-choline), a supplement with α7 nAChRs agonist properties, on SG in a sample of schizophrenia (SZ) patients. Using a randomized, placebo-controlled, double-blind design the dose-dependent (500 mg, 1000 mg, 2000 mg) and baseline-dependent (deficient versus normal suppressors) effects of CDP-choline on SG were examined using the P50 event-related potential (ERP) index of SG. Overall analysis failed to demonstrate treatment effects but CDP-choline improved SG (500 mg) in the deficient SZ subgroup by increasing suppression of the S2 P50 amplitude. These findings tentatively support α7 nAChR dysfunction in the expression of SG deficits and suggest further trials to assess the effects of sustained α7 nAChR activation on SG with low doses of CDP-choline.